2021
DOI: 10.1021/acsnano.0c08075
|View full text |Cite
|
Sign up to set email alerts
|

An Ultrafast WSe2 Photodiode Based on a Lateral p-i-n Homojunction

Abstract: High-quality homogeneous junctions are of great significance for developing transition metal dichalcogenides (TMDs) based electronic and optoelectronic devices. Here, we demonstrate a lateral p-type/intrinsic/n-type (p-i-n) homojunction based multilayer WSe2 diode. The photodiode is formed through selective doping, more specifically by utilizing self-aligning surface plasma treatment at the contact regions, while keeping the WSe2 channel intrinsic. Electrical measurements of such a diode reveal an ideal rectif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
124
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 91 publications
(125 citation statements)
references
References 60 publications
(98 reference statements)
1
124
0
Order By: Relevance
“…The high Se/Pt ratio was realized by a slow cool down process with a continuous supply of Se precursor, while the low Se/Pt ratio was achieved by a rapid cool down process followed by Se precursor removal. Besides the in-situ growth presented above, the defects could be also created by post-growth approaches, that all have the advantage of patterned doping capability, for instance, chemical treatment [66], plasma or electron beam etching [68,70,71], and light illumination [72]. A great example of chemical treatment for the intrinsic defect tailoring of MoS2 is presented in Fig.…”
Section: Intrinsic Defect Tailoringmentioning
confidence: 99%
See 3 more Smart Citations
“…The high Se/Pt ratio was realized by a slow cool down process with a continuous supply of Se precursor, while the low Se/Pt ratio was achieved by a rapid cool down process followed by Se precursor removal. Besides the in-situ growth presented above, the defects could be also created by post-growth approaches, that all have the advantage of patterned doping capability, for instance, chemical treatment [66], plasma or electron beam etching [68,70,71], and light illumination [72]. A great example of chemical treatment for the intrinsic defect tailoring of MoS2 is presented in Fig.…”
Section: Intrinsic Defect Tailoringmentioning
confidence: 99%
“…metal oxides [70,121,[139][140][141], metal halide [125][126][127][128][129][130], organic molecules [125, 134-136, 146, 149, 150, 152], etc. Surface deposition/coating has the advantages of patterned doping capability, relative low doping temperature, and little crystal damage [129,133,134,153].…”
Section: Surface Deposition/coatingmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been demonstrated that through contact engineering by tuning the work function of electrode contact layer, it is able to construct the p‐type contact and result in the fabrication of p‐type transistor. [ 13–15 ] Molecular doping, such as fluoro‐based polymer, could also realize the formation of p‐type electrical property. [ 16–19 ] However, the stability of the adsorbed molecular is still a challenge.…”
Section: Introductionmentioning
confidence: 99%